Healthy Cities : The Theory, Policy, and Practice of Value-Based Urban Planning - de Leeuw, Evelyne; Simos, Jean (Springer New York : Imprint: Springer, 2017)
This forward-looking resource recasts the concept of healthy cities as not only a safe, pleasant, and green built environment, but also one that creates and sustains health by addressing social, economic, and political conditions. It describes collaborations between city planning and public health creating a contemporary concept of urban governance-a democratically-informed process that embraces values like equity. Models, critiques, and global examples illustrate institutional change, community input, targeted assessment, and other means of addressing longstanding sources of urban health challenges. In these ambitious pages, healthy cities are rooted firmly in the worldwide movement toward balanced and sustainable urbanization, developed not to disguise or displace entrenched health and social problems, but to encourage and foster solutions. Included in the coverage: Towards healthy urban governance in the century of the city Healthy cities emerge: Toronto, Ottawa, Copenhagen The role of policy coalitions in understanding community participation in healthy cities projects Health impact assessment at the local level The logic of method for evaluating healthy cities Plus: extended reports on healthy cities and communities in North and Latin America, Africa, Europe, Asia, Oceania, and the Middle East Healthy Cities will interest and inspire community leaders, activists, politicians, and entrepreneurs working to improve health and well-being at the local level, as well as public health and urban development scholars and professionals.- Resumé vydavatel